PEMANFAATAN BAKTERIOFAG UNTUK PENGEMBANGAN KIT DETEKSI BAKTERI PENYEBAB HAWAR BAKTERI PADA KEDELAI - Farid.MS, Moh. Miftah; Susianto, Galih; Dhany, Nurul Rama; Azizi, Norita Fatatik; Resita, Sela Reza (Program Kreativitas Mahasiswa - Penelitian, 2013)
Bacterial leaf blight disease is one of the important soybean disease caused by Pseudomonas syringae that causes about 20% of yield loss. Bacteriophages can be used for therapy to human, animal, and plant against some bacterial pathogens. Due to the specificity of the target bacteria, bacteriophages can be beneficial for detection of the target bacteria. This research was conducted to obtain the particles of bacteriophage, to study their hosts range against several bacterial strains and to formulate a detection kit of bacterial leaf blight. Isolation of bacteria and bacteriophage was obtained from the soybean field and formulation of bacteriophage for detection kit was done on Laboratory of Virology. The results showed that there were 11 isolates of Pseudomonas syringae, 3 particles of bacteriophage (ÏGH1, ÏGH2 and ÏGH3), and detector paper kit. The result also showed that the composition of the detector materials (Talk, CMC, pH indicators) affect the quality of the kit.Â Keywords: bacteriophages, bacterial leaf blight, Psedomonas syringae, Detector